Variability Studies on Pod and Seed Characteristics of Acacia nilotica (L.) Wild Ex. Del. - Chhillar, S; Hooda, M S; Chopra, D (Annals of Arid Zone, 2016)
Genetic variability and correlation in different pod and seed characters of Acacia nilotica were studied. High values of heritability were observed for all the characters, except seed width (23.52%) and seed length (45.2%), while high genetic advance was observed for vigor index-II, vigor index-I, shoot length, seedling dry weight and root length. One hundred seed weight had significant positive correlation with all the characters except seed per pod and electrical conductivity. Seed per pod had non-significant positive correlation with lOG-seed weight, while EC had significantly negative correlation with all the characters.